Anionic vinyl polymerization - 50 years after Michael Szwarc - Baskaran, Durairaj; Mueller, Axel H. E. (Progress in Polymer Science, 2007)
We present a review on the present status of anionic polymerization of important non-polar and polar vinyl monomers. After presenting the historical background-the ``pre-Szwarc'' era-we discuss the mechanisms of this polymerization, in particular several types of carbanions, their ion-pairs and their aggregates occurring in the initiation and propagation of non-polar and polar monomers, including recent developments. Finally, we discuss some important scientific and industrial applications of anionic polymerization. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Anionic polymerization; carbanions; history; ion-pairs; kinetics; mechanisms